Eosinophilic Esophagitis - T Yuli Pramana; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2007)
The frequency of eosinophilic esophagitis (EE) cases is increasing along with increased understanding among doctors about EE. In the beginning, EE is mostly found in children population. It was first reported in adults by Landres on 1978. The prominent EE symptoms in adults are dysphagia and solid food impaction. Endoscopic examination reveals mucous ring of esophagus, white plaque on the mucosa. The diagnosis is supported by positive result of eosinophils, which forms infiltration on the mucosaof 20 eosinophils/ high power field in the distal or middle esophagus. Treatment by using diet and corticosteroid, either topical or systemic, shows adequate results. Immunomodulator treatment is promising, but it needs further investigation with larger sample. No consensus have been reached for EE, therefore it may affect the diagnosis, treatment and epidemiology data.   Keywords: esophagus, eosinophil, dysphagia, ring of esophagus